African biblical hermeneutics in a state of flux – towards refocusing its trajectory - Mojola, Aloo Osotsi (Verbum et ecclesia, 2022)
This study attempts to critically re-examine certain key hermeneutical concerns of a representative group of African biblical and religious studies scholars, who ground African theological reflection on traditional African values, cultures and social realities. Most of the scholars examined are united by a focus on the past and by an attempt to interpret the present and future on the basis of it. The article critiques the backward-looking hermeneutic implicit in the work of the scholars, especially Jesse Mugambi’s backward-looking metaphor of reconstruction. It proposes a hermeneutic based on the metaphor of liberation, as employed, for example, by African women theologians or by Gerald West or Emmanuel Katongole, who focus on building the present and future on the basis of a new liberative transformative narrative and praxis that prioritises the sacredness and inviolability of human life in the context of the web of life, and in particular foregrounds the dignity of African lives, as well as all others. Intradisciplinary and/or interdisciplinary implications: The article engages exposition and understanding of biblical texts by African scholars. Aspects of NT Christology or Ecclesiology are connected to theologies of traditional African socio-cultural realities. The relevance for an African theology of liberation and African theology of women is defended as necessitated by a new liberative transformative hermeneutic.